Perian Semantik Leksem Alat-Alat Pengolah Sagu dalam Bahasa Sentani, Papua - Normawati Normawati (Kelasa, 2019)
Sagoo is a kind of staple food for people in eastern Indonesia. This short writing makes an effort to study any various semantical lexeme of sagoo processing tools in Sentani language, Papua. The stage of this research consist of collecting data, analyzing data and presenting data analysis. Then, she got oral and written data for this research. Those data, then, has been analyzed using analysis of lexical components method by several phase. First, selecting data to determine any meaning class which is mutually collocated and presumed to form a specific domain.  Second, determine contiguity relationship intersense in several lexemes.  Analysis result shows that various semantical lexeme in Sentani language for these tools are eleven lexemes. Those are classified into three groups. They are (1) tools or equipment for cutting sago tree, (2) tools for pounding, and (3) tools for squeezing sagoo. Subdomain meaning of ‘tools for cutting sagoo tree’ lexemes are devided into three, namely, ramayali ‘machete’, ramekahu ‘axe’, and onggi ‘crowbar’.  AbstrakSagu bagi orang Indonesia Timur merupakan salah satu makanan pokok. Tulisan ringkas ini berupaya mengkaji varian semantik leksem alat-alat pengolah sagu dalam bahasa Sentani, Kabupaten Jayapura, Papua. Langkah kerja penelitian ini, meliputi pengumpulan data, pengolahan data, dan pemaparan hasil pengolahan data. Data diperoleh dari data lisan dan data tertulis. Data yang telah terkumpul kemudian dianalisis dengan menerapkan metode analisis komponen leksikal dengan langkah-langkah berikut. Pertama, menyeleksi data untuk menentukan kelompok makna saling berkolokasi yang diperkirakan membentuk satu medan makna tertentu. Kedua, menentukan hubungan kontinguitas antarmakna yang terdapat dalam sejumlah leksem.  Hasil analisis menunjukkan bahwa varian semantik leksem alat-alat pengolah sagu dalam bahasa Sentani berjumlah sebelas leksem. Leksem-leksem tersebut diklasifikasikan ke dalam tiga kelompok, yaitu (1) peralatan dalam menebang sagu, (2) peralatan dalam proses menokok sagu, dan (3) peralatan dalam proses meramas sagu.